Effects of carbon and oxygen on the spark plasma sintering additive-free densification and on the mechanical properties of nanostructured SiC ceramics. Issue 13 (November 2015) - Lanfant, B.; Leconte, Y.; Bonnefont, G.; Garnier, V.; Jorand, Y.; Le Gallet, S.; Pinault, M.; Herlin-Boime, N.; Bernard, F.; Fantozzi, G.
Abstract: Oxygen impurity in SiC nanopowders induces grain growth and porous structure by reacting with SiC upon sintering. As this impurity cannot be avoided in such high specific surface materials, it is interesting to study the parameters that influence its reaction with SiC. Free C is another impurity frequently encountered in carbide materials that influences sintering and mechanical properties. In this context, β-SiC nanopowders were synthesized with controlled composition by laser pyrolysis in order to tune free C and O contents after air exposure. In spite of the absence of sintering additives, high densification (95.6%, grain size below 100 nm) and interesting mechanical properties were obtained (hardness 2150 Hv, toughness 3 MPa m 1/2 ). The influence of SPS parameters on the progression of SiC/C/O reactions was successfully highlighted. The presence of free C, while presenting the advantage of limiting grain growth, tends to impede densification and degrade mechanical properties.